Motivations for Women Involvement in Urban Agriculture in Nigeria - Adebisi , Adedayo; Monisola , Tunde Afolabi (Asian Journal of Agriculture and Rural Development, 2012)
Poverty and food insecurity are some of the problems facing Nigerian population and governments at various levels today. Urban agriculture holds promise at solving these intractable problems. Urban agriculture is a practice that takes place in all urban centres, but existing studies have not succinctly examined the involvement of women in agriculture in small urban centres of Nigeria. The aim of this paper therefore, is to examine the motives behind involvement of women in urban agriculture in small agro-towns of Kwara State, Nigeria. A total of 1,801 women farmers were selected from 13 settlements cutting across 8 LGAs. Simple percentages, graphic illustrations, charts, tabulation and cross tabulation and stepwise multiple regression analysis were used to analyze the generated data. The study identifies three factors: food security, income supplement and accessibility to land, accounting for 98.6% as the best predictors of women involvement in urban agriculture. The study recommends that urban agriculture should be given official recognition by advocating for its support while women should be provided with financial resources to expand their farm plots.